2021
DOI: 10.1186/s12859-021-04064-0
|View full text |Cite
|
Sign up to set email alerts
|

WALTER: an easy way to online evaluate telomere lengths from terminal restriction fragment analysis

Abstract: Background Telomeres, nucleoprotein structures comprising short tandem repeats and delimiting the ends of linear eukaryotic chromosomes, play an important role in the maintenance of genome stability. Therefore, the determination of the length of telomeres is of high importance for many studies. Over the last years, new methods for the analysis of the length of telomeres have been developed, including those based on PCR or analysis of NGS data. Despite that, terminal restriction fragment (TRF) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…Telomere lengths and telomerase activities were then analysed in pptr and WT plants in parallel. While the mean telomere lengths, obtained using terminal restriction fragment length analysis followed by evaluation using WALTER tool ( 36 ), showed values of 1.4 and 1.5 kb in two independent WT plants, mean telomere lengths in three pptr lines revealed values of ca. 300 and 480 bp, respectively (Figure 8A , B), thus corresponding to ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Telomere lengths and telomerase activities were then analysed in pptr and WT plants in parallel. While the mean telomere lengths, obtained using terminal restriction fragment length analysis followed by evaluation using WALTER tool ( 36 ), showed values of 1.4 and 1.5 kb in two independent WT plants, mean telomere lengths in three pptr lines revealed values of ca. 300 and 480 bp, respectively (Figure 8A , B), thus corresponding to ca.…”
Section: Resultsmentioning
confidence: 99%
“…Telomere signals were visualized using a PhosphoImager FLA-7000 (GE Healthcare). Telomere lengths were calculated by WALTER toolset v2.0 ( 36 ) using default setup with background correction.…”
Section: Methodsmentioning
confidence: 99%
“…2B). Southern blot WALTER densitometry profiles (Lycka et al 2021) versus the nanopore data also showed similar profiles between Southern density distribution and the nanopore length distribution (Supplemental Fig. S3B), suggesting that nanopore sequencing can accurately measure telomere fragment length in a bulk population or single telomere population across different telomere length profiles.…”
Section: Telomere Length By Nanopore Sequencing Recapitulates Length Measurement By Southern Blotmentioning
confidence: 65%
“…S2A). We used WALTER , a tool for Southern blot densitometry, that generates summary length statistics (Lycka et al 2021), to compare Southern blot and nanopore telomere length profiles, and again saw comparable profiles (Supplemental Fig. S3A).…”
Section: Telomere Length By Nanopore Sequencing Recapitulates Length Measurement By Southern Blotmentioning
confidence: 94%
See 1 more Smart Citation